Analysis of China’s Low-Carbon Power Transition Path Considering Low-Carbon Energy Technology Innovation - Peng Xia; Gang Lu; Bo Yuan; Yichun Gong; Haitao Chen (Applied Sciences)
Innovation in key low-carbon technologies plays a supporting role in achieving a high-quality low-carbon transition in the power sector. This paper aims to integrate research on the power transition pathway under the “dual carbon” goals with key technological innovation layouts. First, it deeply analyzes the development trends of three key low-carbon technologies in the power sector—new energy storage, CCUS, and hydrogen energy—and establishes a quantitative model for their technological support in the low-carbon transition of the power sector. On this basis, the objective function and constraints of traditional power planning models are improved to create an integrated optimization model for the power transition pathway and key low-carbon technologies. Finally, a simulation analysis is conducted using China’s power industry “dual carbon” pathway as a case study. The optimization results include the power generation capacity structure, power generation mix, carbon reduction pathway, and key low-carbon technology development path for China from 2020 to 2060. Additionally, the impact of uncertainties in breakthroughs in new energy storage, CCUS, and hydrogen technologies on the power “dual carbon” pathway is analyzed, providing technological and decision-making support for the low-carbon transition of the power sector.